Effects of lime and phosphorus rates on growth of hybrid Arabica coffee seedlings at Jimma, southwest Ethiopia - Teshale, E.; Kufa Obso, T.; Regassa, A. (International Institute for Science, Technology and Education, 2019)
Coffee growing soil of southwestern region parts of Ethiopia are classified as Nitisols with having a low pH and highly deficient in phosphorus. A nursery experiment was conducted at Jimma Agricultural Research Center, southwestern Ethiopia to evaluate the effects of lime and phosphorus rates on coffee seedling growth under nursery conditions. The experiment was laid out in a randomized complete block design with 3 replications. The treatments were arranged in factorial combinations of five levels of lime (0, 5, 10, 15 and 20 g) and four levels of phosphorus (0, 400, 600 and 800 mg) 2.5 kg-1top soil. The statical data was analyzed through SAS software and treatment means were compared at 5% probability using Duncan Multiple Range Test. The results revealed that the interactions of lime and P rates significantly increased the growth of both non-destructive parameters (plant height, girth, number of nods, interned length, leaf number and leaf area) and Root growth parameters (taproot length, lateral root length, lateral root number, root volume, leaf stem and root fresh weight, of coffee seedlings. The maximum shoot and root extensions were obtained from the interaction of 10 g lime and 800 mg P rates 2.5 kg-1top soil. On the other hand, applications of P significantly (P≤ 0.01) affected soil and plant growth parameters. As P rate increased availability P boosted and plant growth were enhanced. Similarly, an application of lime significantly affected (P≤ 0.01) plant growth and enhance nutrient availability up to 10 g, though further applications adversely affect seedling growth and nutrient availability. Hence, combined application of 10 g lime and 800 mg P rate 2.5 kg-1top enhances the optimum growth of coffee seedlings under nursery conditions.